Co-branding partner selection: The importance of belief revision - Lee, Chia-Lin; Decker, Reinhold (Journal of Business Economics and Management, 2016)
This paper applies the stereotype change theory to help bridge a major literature gap on co-branding partner selection: why both identical and highly different brand pairs often fail. We argue that, given that a primary goal of establishing a co-branding alliance is to positively revise consumers’ beliefs about important attributes of the allying brands, the case of no belief-revision can lead to a failure of the alliance. We show that both an identical and a highly incongruent partnership in terms of attribute-level difference can fail due to the lack of belief-revision. We report that a moderately incongruent brand pair is a promising decision on co-branding partner selection. In doing so, our research contributes to the explanation of why the two “extreme” types of co-branding alliances may fail from the perspective of consumer evaluation. For brand managers, we offer a normative guideline for co-branding partner selection.